A Prevalence of Refractive Error and Color Vision Caracteristics in Two Elementary School at Kebon Jeruk - Aslamia, Aulia; Silaen, Desi Hartati; Hudyono, Johannes (Universitas Kristen Krida Wacana, 2025)
Refractive errors and color vision deficiencies are common visual health issues among school-aged children and can negatively affect learning performance and quality of life. Early detection is essential to minimize their academic impact. This study aims to determine the prevalence of refractive errors and the characteristics of color vision among students at two public elementary schools at Kebon Jeruk in 2025. This is a descriptive study using a quantitative approach. Data were collected through visual acuity tests using a Snellen chart and color vision screening using Ishihara test book on students who met the inclusion criteria. Of the 792 students examined, the prevalence of refractive errors was 458 (57.8%). The most common type of refractive error was myopia with astigmatism 203 (25.66%), followed by astigmatism 144 (18.20%), myopia 77 (9.70%), hypermetropia with astigmatism 25 (3.20%) and hypermetropia 9 (1.1%). Meanwhile, color vision deficiencies were found in 16 (2%) , all of whom were male and had protan and deutan types. The prevalence of refractive errors among elementary school students is relatively high, while color vision deficiencies are less common. Based on the research results, regular eye examinations and education about eye health are crucial for early detection and treatment to support students' learning process.